KIP-K STUDENTS’ PERCEPTIONS: EVALUATING THE TRANSFORMATION OF RELIGIOUS GUIDANCE AT MA’HAD AL-JAMI’AH, UIN RADEN INTAN LAMPUNG - Rangga Aditia; Umi Hijriyah; Sunarto (QANUN: Journal of Islamic Laws and Studies, 2026)
This study aims to describe the perceptions of students receiving the Indonesia Smart College Card Program (KIP-K) regarding the implementation of religious guidance at Ma’had Al-Jami’ah of UIN Raden Intan Lampung and its impact on their religious attitudes and practices. This research employs a descriptive qualitative approach, involving all KIP-K recipient students residing in the Ma’had as the population, with the sample selected through purposive sampling. Data were collected through semi-structured interviews, participatory observation, and documentation of the guidance activities, and were subsequently analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through technique triangulation. The findings indicate a transformation in students' religious behaviors due to the guidance program. Specifically, students showed increased consistency in performing both obligatory and recommended worship practices, and developed positive habits, such as regularly reciting the Qur’an. The religious guidance, which included halaqah sessions, congregational prayers, classical Islamic text studies, and Qur’anic recitation strengthening, significantly improved students' worship discipline and religious understanding. However, some students faced challenges in balancing academic schedules with the guidance activities, resulting in suboptimal participation in several supplementary programs. Overall, the religious guidance provided at the Ma’had is perceived as relevant and effective in strengthening the religious character of KIP-K recipients. These findings offer an important contribution to the development of more adaptive guidance strategies aligned with the needs of affirmative program beneficiaries in Islamic higher education.